2012
DOI: 10.1111/j.1365-2966.2012.20589.x
|View full text |Cite
|
Sign up to set email alerts
|

NGC 2782: a merger remnant with young stars in its gaseous tidal tail★

Abstract: We have searched for young star‐forming regions around the merger remnant NGC 2782. By using Galaxy Evolution Explorer far‐ultraviolet and near‐ultraviolet imaging and H i data we found seven ultraviolet sources, located at distances greater than 26 kpc from the centre of NGC 2782, and coinciding with its western H i tidal tail. These regions were resolved in several smaller systems when Gemini/Gemini multi‐object spectrograph (GMOS) r‐band images were used. We compared the observed colours to stellar populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 79 publications
3
28
1
Order By: Relevance
“…The internal extinctions (i. e. the color excesses) measured for the star-forming regions in the NGC 6845 system have values E(B-V)=0.50-0.94 that agree with the values found in star forming regions located in other interacting systems e.g. NGC 2856, NGC 2782 and NGC 92 (see Smith et al 2008, Torres-Flores et al 2012.…”
Section: Ages and Internal Extinctions Of The Star-forming Regionssupporting
confidence: 75%
See 1 more Smart Citation
“…The internal extinctions (i. e. the color excesses) measured for the star-forming regions in the NGC 6845 system have values E(B-V)=0.50-0.94 that agree with the values found in star forming regions located in other interacting systems e.g. NGC 2856, NGC 2782 and NGC 92 (see Smith et al 2008, Torres-Flores et al 2012.…”
Section: Ages and Internal Extinctions Of The Star-forming Regionssupporting
confidence: 75%
“…These works were focused on the study of metallicity gradients of interacting galaxies up to twice the optical radii of the galaxies but none of them dealt with galaxies with tidal tails. In an attempt to probe metallicities at increasingly larger radii, our group has focused on deriving metallicity gradients for galaxies with long tidal tails in arXiv:1508.05070v1 [astro-ph.GA] 20 Aug 2015 the optical and Hi as is the case of the galaxies NGC 92 (Torres-Flores et al 2014) and NGC 2782 (Werk et al 2011, Torres-Flores et al 2012. The presence of tidal tails allows probing metallicities not only to much outer radii than in cases of galaxies with no tails, but also in the intragroup medium, where intergalactic Hii regions are found (as it is the case for Stephan's quintet, Trancho et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The H i tidal tails hosts recent star formation: Several star-forming regions were found in the FUV and NUV by Torres-Flores et al (2012) in the western tail, as well as in Hα (Werk et al 2011). Knierman et al (2013) found [C ii] emission at the location of the three most luminous Hα sources in the eastern tail, but also a lack of CO and [C ii] associated with the brighter Hα sources in the western tail.…”
Section: Introductionmentioning
confidence: 99%
“…With the detections of these intergalactic systems, we can analyze the probability to form stellar systems in environments where the gas density, HI ∼ 10 19 cm −2 , is very low. In recent years, various authors reported intergalactic objects in interacting systems with gas tails, such as tidal dwarf galaxies (e.g., Duc & Mirabel 1998;Duc et al 2000;Mendes de Oliveira et al 2001;Hibbard et al 2001;de Mello et al 2012;Lee-Waddell et al 2012) and intergalactic HII regions (e.g., Gerhard et al 2002;Ryan-Weber et al 2004;Mendes de Oliveira et al 2004;Arrigoni Battaia et al 2012;Torres-Flores et al 2012;de Mello et al 2012;Yagi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is commonly observed in pairs or in close interacting galaxies, mainly in the systems, which contain disturbed HI features. Recently, many efforts have been devoted to several systems in the local universe to understand the physical conditions that lead to the formation of new stars and to determine whether these are responsible for polluting the intergalactic medium with metalenriched gas (e.g., Mendes de Oliveira et al 2004); Ryan-Weber et al (2004); Bournaud et al (2004);de Mello et al (2012); Torres-Flores et al (2012); Arrigoni Battaia et al (2012); Yagi et al (2013). These are important points, given that many studies (i.e., Songaila 2001;Pettini et al 2003;Becker et al 2006); Ryan-Weber et al (2006; Simcoe et al (2011);Díaz et al (2011);D'Odorico et al (2013) showed that the intergalactic medium at a redshift of at least 6 is not a pristine remnant of the Big Bang, but rather it contains significant quantities of metals.…”
Section: Introductionmentioning
confidence: 99%